Increased Expression of the Calcium-Activated Chloride Channel in Hclca1 in Airways of Patients with Obstructive Chronic Bronchitis - Hans-Peter Hauber; Celine Bergeron; Anne Tsicopoulos; Benoit Wallaert; Ron Olivenstein; Kenneth J Holroyd; Roy C Levitt; Qutayba Hamid (Canadian Respiratory Journal)
BACKGROUND: Interleukin (IL)-9 and its effect on enhancing the human calcium-activated chloride channel 1 (hCLCA1) expression have been shown to induce mucin production. Increased expression of hCLCA1 may, in turn, contribute to mucus overproduction in chronic obstructive pulmonary disease (COPD) with a chronic bronchitis (CB) phenotype.